PENYIDIKAN TINDAK PIDANA PEMBUNUHAN DI WILAYAH HUKUM KEPOLISIAN SEKTOR PAYUNG SEKAKI DIKAITKAN DENGAN ASAS KEPASTIAN HUKUM - Dinata, Okta Vianda arta; ', Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Today the role of police in criminal criminal cases is very difficult in cases of murder. In the city of Pekanbaru itself the murder case is very large, ranging from ordinary murder to premeditated murder, from such actions criminal law should be active in criminal enforcement and criminal acts of crime, let alone about murder crimes in the city of Pekanbaru, especially in the jurisdiction of Police Sector Umbrella. Will not fall into legal or non-reported channels. Based on the above description, it is interesting to be assembled with the formulation of the problem, how is the investigation of murder crime in the jurisdiction of the police sector of the umbrella sector together with the principle of legal certainty? What are the agreements on the investigation of murder offenses in the jurisdiction of the umbrella-law sector together with the principle of legal certainty? How does the investigation effort in providing legal certainty to murder cases in the jurisdiction of the paramilitary police sector together with the principle of legal certainty?The purpose of this study is to find out how the investigation of murder crime in the jurisdiction of the police of the umbrella sector together with the principle of legal certainty, knowing how to investigate the criminal act of murder and for the investigation of murder crime in the jurisdiction of the umbrella police sector together with the principle of legal certainty.